Environmental tolerances of three species of freshwater crayfish - Firkins, Ian (1993)
The only species of crayfish native to the British Isles, i.e. Austropotamobius pallipes, is presently widely distributed throughout much of England, Wales and Ireland. The main controlling factor behind this distribution is the predominantly "bicarbonate" freshwater system of the British Isles. In geological terms, native crayfish are generally found in areas of chalk, carboniferous or magnesium limestone, or drift deposits of boulder clay. More recently, native crayfish have been affected by a general decline in the quality of Britain's freshwater system largely due to sewage effluent and agricultural. By far the majority of native crayfish records are associated with water bodies of very good or good quality, with the result that many populations of A. pallipes are isolated in small, good quality headwaters, due to the degree of pollution in the main rivers acting as "chemical barriers".